Evaluating the Impact of Primary Tumor Resection on EGFR-TKI-treated Patients with Advanced Lung Cancer: A Multicenter Propensity-matched Study - Eva Yu-Hsuan Chuang; Chiao-En Wu; Tzu-Wei Kuo; Yu-Wen Wen; Ping-Chih Hsu; Chih-Hsi Scott Kuo; Cheng-Ta Yang; Ling-Jen Hung; Yin-Kai Chao (Journal of Cancer Research and Practice)
Background: Nonsmall-cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations is exceptionally sensitive to EGFR tyrosine kinase inhibitors (TKIs). Despite this, disease progression commonly occurs at the primary site, prompting debate on the potential advantages of incorporating primary tumor resection alongside standard maintenance therapy. Materials and Methods: This retrospective multicenter study enrolled NSCLC patients treated with EGFR-TKIs and categorized them into surgery and control groups based on primary tumor resection. The propensity score matching (PSM) method was used to ensure balanced comparisons, accounting for 12 covariates. Progression-free survival (PFS) and overall survival (OS) were evaluated, addressing immortal time bias. Results: Among 2151 EGFR-TKI-treated patients screened from 2010 to 2019, 57 (21 surgery group, 36 control group) were included post-PSM and accounting for immortal time bias. No cases of major complications (grade IIIa or higher based on Clavien-Dindo criteria) or 90-day mortality were noted in the surgery group. Pulmonary resection was significantly associated with longer PFS (58.6 vs. 14.1 months, P = 0.001) and OS (109.6 vs. 46.6 months, P = 0.016) compared to EGFR-TKI monotherapy. Positive outcomes were consistent across diverse subgroups. Conclusion: The addition of primary tumor resection in EGFR-mutant NSCLC patients receiving EGFR-TKI treatment was associated with improved PFS and OS compared to EGFR-TKI treatment alone. However, these results should be interpreted with caution due to potential selection bias in the analysis.